Dysbindin‐1 modifies signaling and cellular localization of recombinant, human D3 and D2 receptors. Issue 5 (21st January 2016) - Schmieg, Nathalie; Rocchi, Cristina; Romeo, Stefania; Maggio, Roberto; Millan, Mark J.; Mannoury la Cour, Clotilde
Abstract: Dystrobrevin binding protein‐1 (dysbindin‐1), a candidate gene for schizophrenia, modulates cognition, synaptic plasticity and frontocortical circuitry and interacts with glutamatergic and dopaminergic transmission. Loss of dysbindin‐1 modifies cellular trafficking of dopamine (DA) D2 receptors to increase cell surface expression, but its influence upon signaling has never been characterized. Further, the effects of dysbindin‐1 upon closely related D3 receptors remain unexplored. Hence, we examined the impact of dysbindin‐1 (isoform A) co‐expression on the localization and coupling of human D2L and D3 receptors stably expressed in Chinese hamster ovary or SH‐SY5Y cells lacking endogenous dysbindin‐1. Dysbindin‐1 co‐transfection decreased cell surface expression of both D3 and D2L receptors. Further, while their affinity for DA was unchanged, dysbindin‐1 reduced the magnitude and potency of DA–induced adenylate cylase recruitment/cAMP production. Dysbindin‐1 also blunted the amplitude of DA‐induced phosphorylation of ERK1/2 and Akt at both D2L and D3 receptors without, in contrast to cAMP, affecting the potency of DA. Interference with calveolin/clathrin‐mediated processes of internalization prevented the modification by dysbindin‐1 of ERK1/2 and adenylyl cyclase stimulation at D2L and D3 receptors. Finally, underpinning the specificity of the influence of dysbindin‐1 on D2L and D3 receptors, dysbindin‐1 did not modify recruitment of adenylyl cyclase by D1 receptors. These observations demonstrate that dysbindin‐1 influences cell surface expression of D3 in addition to D2L receptors, and that it modulates activation of their signaling pathways. Accordingly, both a deficiency and an excess of dysbindin‐1 may be disruptive for dopaminergic transmission, supporting its link to schizophrenia and other CNS disorders. Dysbindin‐1, a candidate gene for schizophrenia, alters D2 receptors cell surface expression. We demonstrate that dysbindin‐1 expression also influences cell surface levels of D3 receptors. Further, Dysbindin‐1 reduces DA‐induced adenylate cylase recruitment/cAMP production and modifies major signaling pathways (Akt and extracellular signal‐regulated kinases1/2 (ERK1/2)) of both D2 and D3 receptors. Dysbindin‐1 modulates thus D2 and D3 receptor signaling, supporting a link to schizophrenia. Abstract : Dysbindin‐1, a candidate gene for schizophrenia, alters D2 receptors cell surface expression. We demonstrate that dysbindin‐1 expression also influences cell surface levels of D3 receptors. Further, Dysbindin‐1 reduces DA‐induced adenylate cylase recruitment/cAMP production and modifies major signaling pathways (Akt and extracellular signal‐regulated kinases1/2 (ERK1/2)) of both D2 and D3 receptors. Dysbindin‐1 modulates thus D2 and D3 receptor signaling, supporting a link to schizophrenia.